Frekuensi Latihan Fisik, Durasi Tidur, dan Performa Neurokognitif: Analisis Cross-Sectional Terhadap Inhibisi Kognitif dan Kecepatan Pemrosesan pada Mahasiswa Ilmu Keolahragaan - Septian Williyanto; Herman Subarjah; Surdiniaty Ugelta; Sri Nurlatipah; Danang Isworo Wijayanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine the relationships between exercise frequency and sleep duration with cognitive inhibition and information processing speed among sport science undergraduates. A cross-sectional design was employed involving 45 sport science undergraduates (28 males, 17 females; mean age 19.62 ± 0.72 years; mean BMI 21.79 ± 2.49 kg/m²). Exercise frequency (sessions/week) and sleep duration (hours/night) were self-reported. Neurocognitive function was assessed using the Stroop Color-Word Test (inhibitory control) and the Trail Making Test (processing speed). Pearson correlation and multiple linear regression analyses were used to determine the associations. The results showed that: (1) exercise frequency had a significant positive correlation with Stroop scores (r = 0.545, p < 0.001); (2) sleep duration was significantly correlated with both Stroop scores (r = 0.479, p = 0.001) and TMT performance (r = -0.356, p = 0.016); (3) exercise frequency and sleep duration jointly explained 29.3% of the variance in inhibitory control (R² = 0.325, R²adj = 0.293); and (4) both variables explained 9.0% of the variance in processing speed (R² = 0.132, R²adj = 0.090). It can be concluded that exercise frequency and sleep duration are positively associated with cognitive inhibition among sport science undergraduates, while sleep duration alone predicts processing speed. These findings support the integration of sleep hygiene education and structured exercise programs into sport science curricula to optimize students' neurocognitive performance. Keywords: Sleep Duration, Exercise Frequency, Neurocognitive Function, Sport Science, Cognitive Inhibition, Processing Speed, Stroop Test, Trail Making Test